Thiol-reactive molecule with dual-emission-enhancement property for specific prestaining of cysteine containing proteins in SDS-PAGE - Yu, Yong (2013)
1-[4-(Bromomethyl)phenyl]-1,2,2-triphenylethene (2) was synthesized and evaluated for specific fluorescent prestaining of proteins containing cysteine (Cys) in SDS-PAGE. The molecule showed classic aggregation-induced emission (AIE) property in protein labeling and its quantum efficiency was further enhanced upon reacting with Cys. The parameters of reaction such as labeling time and concentration of dye and reducing reagent-tris(2-carboxyethyl)phosphine (TCEP) were examined to obtain the optimal labeling condition. In addition to its specific labeling effect, molecule 2 also showed its advantage over traditional self-quenching dyes through labeling Cys containing BSA with different dye/Cys ratios.